Zingiber calcicola (Zingiberaceae), a new species from a limestone area in south Yunnan, China - Ding, Hong-Bo; Quan, Dong-Li; Zeng, Xiao-Dong; Li, Jian-Wu; Tan, Yun-Hong (Phytotaxa, 2021)
Zingiber calcicola Y.H.Tan & H.B.Ding, sp. nov. (Zingiberaceae) from a limestone area in south Yunnan, China is described and illustrated here. It belongs to Zingiber sect. Dymczewiczia due to the terminal inflorescence on the leafy shoot. The description, photographs, habitat, distribution, phenology and a comparison with the allied species are also provided.